Filmes de ZnO contendo nanopartículas de ouro depositados em materiais magnéticos : síntese e eficiência na fotodegradação catalítica de corantes têxteis - Silva, Robes Alves da (2018)
This study shows the synthesis, characterization and photocatalytic efficiency of ZnO coated semiconductor magnetic films obtained through a new chemical manufacturing approach assisted by the thermo decomposition of urea in aqueous solutions, which provided a controlled increase in pH and rendered a superior adhesion of the ZnO phase around the magnetite nanoparticles (Fe3O4) as a great advantage over other types of commonly used alkaline agents such as NaOH and NH4OH. This material (Fe3O4@mZnO) was used as a solid support for the anchoring of highly dispersed gold (Au) nanoparticles (≈5 nm) on its surface forming the hybrid (Fe3O4@mZnO@Au) enhancing the catalytic activity. The solids were characterized by Transmission Electron Microscopy (TEM), High Resolution Transmission Electron Microscopy (HRTEM), X-ray Dispersive Spectroscopy (EDS) X-ray Diffraction Spectroscopy (DRX), Lightning Photoelectron Spectroscopy (XPS), UV-Vis Spectroscopy, Vibrant Sample Magnetometry (VSM), Inductive Coupling Plasma Atomic Emission Spectroscopy (ICP-AES) by the Brunauer method, Emmett, Teller (BET) to obtain a complete physical and morphological profile. In order to evaluate the efficiency of the photocatalytic activity of the materials the decomposition reaction of the textile dye rhodamine B in aqueous solutions at 15º C was used and could be quickly separated by the application of a neodymium magnet in contact with the wall of the reactor, which made possible the reuse of these nano catalysts in up to 12 cycles, dispensing more costly and less adequate methods of separation. Monitoring leaching of free Zn species during catalyst manufacture suggests that the use of urea substantially decreased the formation of non-magnetic species and provided a higher mass yield of the magnetic composite compared to an analog protocol using NaOH and as a consequence a higher photocatalytic efficiency. Since the material decorated with Au NPs made it even more promising in the photocatalytic activity under visible artificial light.